2008
DOI: 10.1007/s11055-008-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuron density in the hippocampus in rat strains with contrasting nervous system excitability after prolonged emotional-pain stress

Abstract: A model system consisting of two rat strains bred for nervous system excitability in response to electric shocks was used to study changes in the number density of neurons in hippocampal field CA3 at 24 h, two weeks, and two and six months after prolonged emotional-pain stress (PEPS). Neuron density in hippocampal field CA3 decreased after completion of PEPS. These changes arose at different time points in the different rat strains (one day for low-excitability rats, two months for high-excitability rats) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Microinjections of a low dose of propranolol in the dorsal hippocampus induce different changes in c‐Fos expressions in hippocampal subregions via their internal neural pathways. In addition, based on the results from animal studies, stress‐related hippocampal damage primarily occurs in certain subfields (Duan, Kang, Liu, Ming, & Song, ; Shiryaeva, Vshivtseva, Mal’ Tsev, Sukhorukov, & Vaido, ). Specifically, we think the early use of low‐dose propranolol may selectively affect certain subfields, such as the CA1 and the DG, while sparing the CA3 region.…”
Section: Discussionmentioning
confidence: 99%
“…Microinjections of a low dose of propranolol in the dorsal hippocampus induce different changes in c‐Fos expressions in hippocampal subregions via their internal neural pathways. In addition, based on the results from animal studies, stress‐related hippocampal damage primarily occurs in certain subfields (Duan, Kang, Liu, Ming, & Song, ; Shiryaeva, Vshivtseva, Mal’ Tsev, Sukhorukov, & Vaido, ). Specifically, we think the early use of low‐dose propranolol may selectively affect certain subfields, such as the CA1 and the DG, while sparing the CA3 region.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal density in the CA3 area of the hippocampus was also shown to be significantly reduced in rats after prolonged pain stress in the form of 13 min electric shocks for 15 days [28]. It has been proposed that alterations in the cholinergic neurotransmitter systems due to stress are the initial events contributing to CNS impairment and that exacerbation of injury could occur with the concurrent exposure of stress and cholinesterase inhibitors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, examining the effects of early stress on different hippocampal subfields may clarify the role of early stress on hippocampus and related behavior. Animal research showed that stress was related specifically to damage in the dentate gyrus, which contains multipotent adult neural stem cells and is thus the key region for neurogenesis 53 , 54 , and the CA3 subfield, which is the main target for glucocorticoids 55 , 56 . For example, rats subjected to physical restraint showed reduced branching and atrophy in CA3 57 and tree shrews exposed to chronic psychosocial stress showed reduced dendritic length and number of branch points in CA3 14 .…”
Section: Introductionmentioning
confidence: 99%